Household dietary patterns and the cost of a nutritious diet in Myanmar - Mahrt, Kristi; Mather, David; Herforth, Anna; Headey, Derek D. (International Food Policy Research Institute, 2019)
Despite significant poverty reduction over the past decade, undernutrition in Myanmar remains widespread. Food prices play an important role in influencing diets and nutrition outcomes, especially for poorer households. In this study, we use national household food expenditure data to assess dietary patterns and estimate regional costs of nutritious diets in Myanmar relative to a recommended diet derived from food-based dietary guidelines. We estimate these costs following the cost of a recommended diet method (CoRD), which is based on minimum food group prices. We also develop and demonstrate an extension of this method using food group prices that reflect typical food consumption preferences (CoRD-FP). We assess the affordability of the recommended diet by comparing observed household food expenditure to the CoRD and the CoRD-FP. In 2015, 52 percent of the Myanmar population lived in households with food expenditure below the CoRD-FP, compared to 70 percent in 2010. Even the CoRD, which measures the lowest possible cost of meeting the recommended diet, exceeded household food expenditure for 32 and 24 percent of the population in 2010 and 2015, respectively. Low affordability is driven by high costs of animal-source foods and vegetables, which account for half the CoRD-FP. A majority of households over-consume staples and under-consume micronutrient-dense food groups. This imbalance is driven in part by the high caloric price of nutrient-dense foods relative to rice. The inability of more than half of households in Myanmar to afford a recommended diet at existing food expenditure levels suggests the need for policies that reduce the prices of micronutrient-dense foods, ideally through pro-poor improvements in agricultural productivity and marketing.